2013
DOI: 10.1161/atvbaha.112.301167
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Human Fibroblasts to Functional Endothelial Cells by Defined Factors

Abstract: Objective Transdifferentiation of fibroblasts to endothelial cells (ECs) may provide a novel therapeutic avenue for diseases including ischemia and fibrosis. Here we demonstrate that human fibroblasts can be transdifferentiated into functional ECs by using only two factors, Oct4 and Klf4, under inductive signaling conditions. Approach and Results To determine if human fibroblasts could be converted into ECs by transient expression of pluripotency factors, human neonatal fibroblasts were transduced with lenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 32 publications
4
116
0
Order By: Relevance
“…8 The direct conversion of adult cells into ECs can provide new therapeutic modalities to overcome the hurdles associated factors (OCT4, SOX2, KLF4, and c-MYC) 24,25 can convert human fibroblasts into ECs without inducing pluripotent status. [30][31][32] However, because conversion by these techniques involves the generation of intermediate progenitor cells or partial iPSCs, these are essentially different from our direct conversion technology. Moreover, because these studies used pluripotent factors, there are still concerns about their tumorigenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…8 The direct conversion of adult cells into ECs can provide new therapeutic modalities to overcome the hurdles associated factors (OCT4, SOX2, KLF4, and c-MYC) 24,25 can convert human fibroblasts into ECs without inducing pluripotent status. [30][31][32] However, because conversion by these techniques involves the generation of intermediate progenitor cells or partial iPSCs, these are essentially different from our direct conversion technology. Moreover, because these studies used pluripotent factors, there are still concerns about their tumorigenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…After 14 days, the subcutaneous plugs were explanted, and immunostaining was performed using antibody against murine CD31 for identifying the microvessels. Some groups were treated with bFGF as a reference control because bFGF is known to induce an angiogenic response in subcutaneous Matrigel plugs 18. As shown in Figure 10, microvessel density was significantly increased by the treatment of CEP03 (27.6±14/mm 2 ) or bFGF (27.8±18.5/mm 2 ) compared with vehicle control mice that received only Matrigel (4.7±2.5/mm 2 ; P <0.05).…”
Section: Resultsmentioning
confidence: 96%
“…The animals were randomized to receive Matrigel alone (control), bFGF (6 nmol/L), CEP03 (2 mmol/L), or bFGF (6 nmol/L) plus CEP03 (2 mmol/L; n=8 per randomized group). Some groups were treated with bFGF as a reference control because bFGF is known to induce an angiogenic response in subcutaneous Matrigel plugs 18. All reagents were dissolved in Matrigel (Geltrex; Gibco) at 4°C and injected at 300 μL per injection subcutaneously to form a gelatinous plug.…”
Section: Methodsmentioning
confidence: 99%
“…Some pluripotency factors used to produce iPSC can directly reprogram some cell types such as cardiomyocytes (Efe et al, 2011), neural stem cells or progenitors , angioblast-like progenitor cells (Kurian et al, 2013), endothelial cells (Li et al, 2013a), pancreatic lineages , and hepatocytes . Ma et al (2013) showed that pluripotent factors can reprogram adult cells into pluripotent cells with multiple steps and that at certain steps some cells' fates are formed as transition stages of epigenetic reprogramming .…”
Section: Pluripotency Factors For Indirect Reprogrammingmentioning
confidence: 99%